Ensemble Recordings in Awake Rats: Achieving Behvioral Regulatrity during Multimodal Stimulus Processing and Discriminative Learning. - Lee, Eunjeong; Oliveira-Ferreira, Ana I.; Water, Ed de; Gerritsen, Hans; Bakker, Mattijs C.; Kalwij, Jan A. W.; Goudoever, Tjerk van; Buster, Wietze H.; Pennartz, Cyriel M. A. (Journal of the Experimental Analysis of Behavior, 2009)
To meet an increasing need to examine the neurophysiological underpinnings of behavior in rats, we developed a behavioral system for studying sensory processing, attention and discrimination learning in rats while recording firing patterns of neurons in one or more brain areas of interest. Because neuronal activity is sensitive to variations in behavior which may confound the identification of neural correlates, a specific aim of the study was to allow rats to sample sensory stimuli under conditions of strong behavioral regularity. Our behavioral system allows multimodal stimulus presentation and is coupled to modules for delivering reinforcement, simultaneous monitoring of behavior and recording of ensembles of well isolated single neurons. Using training protocols for simple and compound discrimination, we validated the behavioral system with a group of 4 rats. Within these tasks, a majority of medial prefrontal neurons showed significant firing-rate changes correlated to one or more trial events that could not be explained from significant variation in head position. Thus, ensemble recordings can be combined with discriminative learning tasks under conditions of strong behavioral regularity. Reprinted by permission of the publisher.